A LETTER FROM THE GOVERNOR OF BIG BLUE MARBLE SCHOOL FOR MORAL URGENCY, SOUL MAKING AND HUMAN ADVANCEMENTS. Issue 37 (17th March 2014) - Fisher, Tim
<x content-type="archive" xml:space="preserve">Abstract</x> A traditional defense of God in the face of pain and suffering is that humans learn from encounters with suffering – learn something wonderfully valuable that could not be learned in any other way. God is a teacher, and we humans are the students. This article examines the Problem of Evil through this paradigm. It argues that any God-as-teacher defense of evil fails on its face because God does not meet even the most lax standard for teacher behavior and action.